Interferensi dan Integrasi Bahasa Arab terhadap Bahasa Indonesia dalam Wacana Dakwah - Nurhamim Nurhamim (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
In a bilingual society, interference and integration events often occur, both of which are two topics in sociolinguistics that occur due to the use of two or more languages ​​in a bilingual or multilingual speech community. Both are also closely related to the problem of code-switching and code-mixing. Suppose a code-switching is an event of changing language or language variety by a speaker due to specific reasons and is done consciously. At the same time, code-mixing uses fragments from another language in using a language that may be needed. In that case, it is not considered an error or mistake. In interference, Deviation used language and society are two words that cannot be separated. The pronunciation of Arabic words that have been absorbed into Indonesian and are the standard form still spoken using their original form that is Including the symptoms in Indonesian society is fascinating to study. That is a part of language planning. Even saying words in Arabic when the speaker is communicating in Indonesian even though the words spoken already have translations or equivalents in Indonesian.